Finanças Internacionais e Formação do Capitalismo Nacional em Moçambique - Castel-Branco, Carlos Nuno (Desafios para Moçambique 2020, 2020)
Este capítulo descreve e explica como e por que razão a economia moçambicana e as suas dinâmicas de expansão e de crise, as suas contradições e os seus paradoxos foram estruturados e articulados pela sua relação de dependência com o capital financeiro privado internacional, e as implicações desta relação para as características, as dinâmicas e as opções de acumulação privada de capital e de desenvolvimento da sociedade como um todo em Moçambique.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; natural resources / recursos naturais; private sector / setor privado

Corporate Social Responsibility in Mozambique - Kaufmann, Friedrich; Simons-Kaufmann, Claudia (Corporate Social Responsibility in Sub-Saharan Africa: Sustainable Development in its Embryonic Form, 2016)
Mozambique is a young African country with a strong growing economy and increasing foreign direct investment. We can observe a rising number of Corporate Social Responsibility (CSR) projects and activities in the country. Nevertheless there is still no systematic approach or coordination through public authorities or the business sector itself. CSR is mainly motivated by immediate own company needs like training or health of workers. We also find philanthropy projects as well as projects supporting local communities on development priorities, mainly health, education and community development. CSR, as part of a business concept, is mainly limited to large companies and foreign investors with international experience and less to small and medium-sized enterprises (SMEs). Many national companies, especially SMEs still do not have the CSR capacity or the respective mind set. First of all it is the mega projects that have their professional CSR departments and budgets. In the mining sector a CSR component is now compulsory by law since 2014.As public institutions are weak, CSR in Mozambique is more about “CSR towards compliance” and sometimes less about “CSR beyond compliance”. Strong views are expressed by civil society that for example the enforcement of labour legislation within companies is weak and hardly controllable by the government. This fact combined with corruption issues makes CSR towards compliance of existing labour, environmental, fiscal laws and other regulation an important topic. Nevertheless it is questionable if this should be considered as CSR. CSR in general is sometimes seen as “green washing” by big investors, benefitting on the other hand from generous tax exemptions and special deals with the government. Nevertheless, CSR is of growing importance in Mozambique and as the new mining CSR law shows, government is slowly entering the CSR landscape. A better coordination and public-private dialogue about CSR is necessary in order to make it a more useful and an efficient instrument for development. Nevertheless it should be clear that CSR is voluntary and in a globalized economy with international value chains becomes more and more an international issue.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; civil society / sociedade civil; private sector - CSR (corporate social responsibility) / setor privado - RSC (responsabilidade social corporativa); private sector / setor privado

Indústria extractiva e desenvolvimento local: O papel da responsabilidade social empresarial - Langa, Epifânia; Massingue, Nelsa (Desafios para Moçambique, 2014)
A entrada de grandes investimentos de capitais estrangeiros na área de recursos minerais e energia, nos últimos anos, tem levantado várias questões sobre o papel dos mega ‑projectos no desenvolvimento económico e social em Moçambique, gerando um debate sem consenso. Uma das temáticas do debate é a responsabilidade social empresarial (RSE). Acções de RSE como a construção de infra ‑estruturas sociais para a educação e a saúde, a geração de emprego, entre outras são muitas vezes referenciadas em muitos discursos, principalmente políticos e de empresas, como aspectos positivos que complementam as acções do governo, devendo por isso ser promovidas e valorizadas.1 Entretanto, estes discursos muitas vezes negligenciam componentes não menos importantes como a intenção das empresas ao desen‑ volver iniciativas sociais, o risco das comunidades se tornarem dependentes destes mega ‑projectos e a possibilidade de fragilização do papel do Estado (Schroeder & Schroeder, 2004).
Keywords: G - Mozambique / Moçambique; L - portuguese / português; extractive industries / indústrias extractivas; natural resources / recursos naturais; private sector - CSR (corporate social responsibility) / setor privado - RSC (responsabilidade social corporativa); private sector / setor privado